Pemilu 2014: Politisi Pencari Kursi di Senayan - Rahman, Fathur; Ulfah, Irma Fitriana; Danar, Oscar Radyan (Faculty of Social and Political Science Universitas Brawijaya, 2018)
General Elections can be used as evidence as well as evaluation of the recruitment process, political circulation. This paper proves that in the 2014 Election there has been a stagnation in political circulation. As well as, the 2014 elections, where many candidates for peoples representatives are still filled by old politicians. After becoming a member of the House of Representatives for a long time, he became a member of the DPD, and vice versa. As a result, there is still a strong intervention by political parties in placing their cadres. As a result, there is often political decay like corruption.